ASIMETRI INFORMASI DAN PENEKANAN ANGGARAN SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN PADA SENJANGAN ANGGARAN - Diah Lestari, I Gusti Ayu; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2017)
Public sector budget is an instrument of accountability for the management of public funds and the implementation of programs funded with public money. This study aimed to examine the effect of budgetary participation on budgetary slack and asymmetry of information and budget emphasis in moderating influence on budgetary slack budgetary participation in the government of Denpasar. The study was conducted on 33 SKPD Denpasar. Sample selection is done by using purposive sampling method. The number of respondent as many as 99 people consisting of Chief SKPD, Head of Sub. General Section and Planning and Head of the sub. Financial department. Data collected through questionnaires. The analysis technique used in the study is the Simple Linear Regression Analysis and Moderated Regression Analysis The study found a positive effect of participation budgeting on budgetary slack, information asymmetry and budget emphasis strengthen budgetary participation influence on budgetary slack.
Keywords: Budgetary Slack, Budgetary Participation, Asymmetry Information, Budget Emphasis